Femoral Balloon-Oriented Puncture for True Lumen Reentry in the Common Femoral Artery After Subintimal Retrograde Recanalization of Superficial Femoral Artery Ostial Occlusion: The FORLEE Technique. (August 2019) - Testi, Gabriele; Ceccacci, Tanja; Cevolani, Mauro; Giacchi, Francesco; Tarantino, Fabio; Turicchia, Giorgio Ubaldo
Purpose: To report a new technique to reenter the common femoral artery (CFA) true lumen after retrograde recanalization of a superficial femoral artery (SFA) with flush ostial occlusion.Technique: The technique is demonstrated in a 76-year-old woman with critical limb ischemia previously submitted to several surgical revascularizations. A duplex ultrasound showed flush ostial occlusion of the SFA and patency of the anterior tibial artery at the ankle as the sole outflow vessel. After unsuccessful antegrade attempts to recanalize the SFA, a retrograde guidewire was advanced subintimally up to the CFA, without gaining reentry. A balloon catheter was inflated in the subintimal plane across the SFA ostial occlusion. Antegrade access to the distal CFA was achieved with a 20-G needle, which was used to puncture the balloon. A guidewire was advanced into the balloon and pushed forward while the collapsed balloon was pulled back to the mid SFA. The antegrade guidewire was externalized through a retrograde catheter, which was pushed in the CFA true lumen. A retrograde guidewire was advanced and externalized through the femoral sheath, establishing a flossing wire. The procedure was completed in antegrade fashion.Conclusion: The FORLEE technique is a cost-effective option to gain the CFA true lumen after subintimal retrograde recanalization of an ostial SFA occlusion.